An integrated SIW-CDRA array for high-speed 5G and V2X millimeter-wave applications - Mohammed T. A. Alhaddad; Mohd. Haizal Jamaluddin; Hafizal Mohamad (Springer Science and Business Media LLC, 2026)
Tier 2- Indexed by SCOPUS